The development of a digital educational program with parents of preterm infants and neonatal nurses to meet parents educational needs. Issue 1 (February 2021) - Lebel, Valérie; Héon, Marjolaine; Juneau, Audrey Larone; Collette, Kimberley; Feeley, Nancy
Abstract: The aim of this research project is to explore parents and staff opinion about the development of a digital educational program to meet parent's educational needs in neonatology. For this qualitative study, one-on-one and group interviews were conducted in person or via a web platform with 15 mothers, 5 fathers and 9 neonatal nurses. Participants considered the digital educational program presented relevant and complete. They believed the digital educational program should be available as soon as possible for parents, at admission or even before. More than half thought it was better to have the information presented on a website, while an equal number of participants considered an application to be optimal. In addition, participants proposed several additional topics to add, such as information about discharge, resources available in the NICU or after discharge, and breastfeeding complications, among others. In conclusion, a digital educational program addressing topics such as parenting, infants' behaviour and appearance, and the care environment is appropriate to meet the needs of premature infants' parents.